IMPLEMENTASI KEBIJAKAN NOMOR IDENTITAS TUNGGAL: BUKTI TINGKAT LOKAL DARI KOTA MAKASSAR, INDONESIA - Eko Budi Lestari; Eljawati; Restu Widyo Sasongko; Ida Yunari (Jurnal Ilmiah Wahana Bhakti Praja, 2026)
This study focuses on the implementation analysis of the Single Identity Number policy through the matching of the Population Administration Number and the Tax Identification Number at the local level, with Makassar City, Indonesia, as the case study. A qualitative approach in a case study design is employed in this research. Informants in this research are 15 people selected purposively, consisting of officials from the Department of Population and Civil Registration, officials and technical implementers of the Pratama Tax Service Office, administrative service personnel, and members of the public who are taxpayers and have and have not undergone NIK–NPWP matching. The population is all policy actors, implementers, and target groups of the SIN policy in Makassar City. Data collection was carried out through in-depth interviews, non-participant observation, and documentary study, and the validity of data was obtained through triangulation of sources and techniques. Data were analyzed qualitatively using Merilee S. Grindle’s policy implementation framework, focusing on the content of the policy and the context of implementation. The results showed that the NIK–NPWP matching policy has developed normatively and administratively but is still far from optimum due to technical data limitations, weak interagency coordination, and limited awareness and compliance from the public. It is concluded that the local success of the SIN policy depends highly on how the context of implementation is strengthened through cross-sector coordination, demographic data quality improvement, and adaptive socialization strategies. The study suggests strengthening integrated services and improving institutional capacity to optimize SIN policy implementation at the regional level. Keywords: single identity number, policy implementation, population administration, local government.